ICTs and other non-pharmacological interventions for ADHD - Doulou, Aikaterini; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Numerous researches carried out during the last decade have contributed to the fact that we have now enough data concerning the profile and treatment of ADHD. Too often, children with ADHD face problems in learning and behavior due to difficulties in cognitive and metacognitive functions. It is not uncommon for them to be marginalized either at school or in the family due to inappropriate handling and interventions. In order to improve the quality of life of these children and their relationships to adults and peers, it is essential to develop their emotional intelligence and skills such as self-awareness, self-regulation, and self-control. The treatment methods for ADHD usually involve behavior modification, pharmacotherapy, or a combination of both. This paper investigates the use of new technologies for the treatment of ADHD, as well as the effectiveness of behavioral interventions.